PENGARUH KUALITAS PRODUK MAKANAN DAN PELAYANAN TERHADAP KEPUASAN TAMU DI NOSTALGIA RESTAURANT THE SIDJI HOTEL PEKALONGAN - Ika Pratiwi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2021)
This research was conducted at Nostalgia Restaurant The Sidji Hotel Pekalongan which aims to analyze and explain the influence of food product quality and service on guest satisfaction which is experiencing poorly good conditions including color, appearance, portion, tecture, temperature and level of maturity of a food product not in accordance with guest expectations and there are some infrastructure services that do not meet the standards in providing services to guests. The research data were obtained through questionnaires and interviews. The sample used in the study was 100 respondents. The research results are expected to provide useful information for the manager and guest satisfaction. The data obtained were processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis uses multiple regression analysis to determine the effect of the independent variable on the dependent variable, model test, hypothesis testing, and however before the test is carried out, the validity and reliability tests are conducted first. The results of the regression analysis show that there is an increase in the quality of food products and services on guest satisfaction. Then the test results of multiple regression analysis show a significant F value, with a correlation value of determination R2 square of 0.598. This shows that the quality of food products and services significantly affects guest satisfaction together with a close relationship of 59.8%. This shows that to increase guest satisfaction, it is necessary to increase the quality of products, both food and beverages served to guests, as well as excellent service in accordance with guest expectations.